LANGUAGE LEARNING STRATEGIES AND EFL SPEAKING PERFORMANCE: THE MEDIATING ROLE OF SELF-REGULATION AMONG INDONESIAN UNIVERSITY STUDENTS - Finza Larasati; Hadiyanto Hadiyanto; Urip Sulistiyo; Eddy Haryanto (University of Kuningan, 2026)
This study investigates the role of language learning strategies (LLS) in shaping Indonesian EFL learners’ speaking performance by integrating quantitative and qualitative evidence in a mixed-methods design. Specifically, it aims to (1) describe learners’ use of LLS, (2) examine the correlation between LLS and speaking performance, (3) identify the predictive contribution of LLS to speaking outcomes, and (4) explore learners’ strategic experiences in speaking development through responses to open-ended questionnaire items. Eighty undergraduate EFL students participated in the study. Quantitative data were collected using the Strategy Inventory for Language Learning (SILL) and a speaking performance test, while qualitative data were obtained from learners’ open-ended responses about how they used strategies in practice. The quantitative results revealed a very strong positive correlation between LLS and speaking performance (r = .912, p < .001), indicating that students who employed strategies more frequently tended to achieve higher speaking scores. Multiple regression analysis showed that no single LLS category uniquely predicted speaking performance due to severe multicollinearity among strategy types, suggesting that LLS operate as an integrated, interdependent system rather than isolated components. Descriptive results indicated that cognitive strategies were the most dominant, while qualitative evidence showed that learners actively combined cognitive, metacognitive, social, and affective strategies including repeated practice, imitation, planning, self-monitoring, and peer interaction. Learners demonstrated strong self-regulation in overcoming challenges and benefited from teacher feedback, peer support, and technological tools. Overall, the findings highlight that strategic behavior is crucial for enhancing speaking fluency, accuracy, and confidence, implying that EFL instruction should explicitly foster strategic awareness and provide supportive learning environments to optimize speaking development.